PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN013BALAMJAYA KECAMATAN TAMBANG - NOPRI YANTI; HENDRI MARHADI; LAZIM N LAZIM N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractProblem on this research was that student’s achievement on natural sciences at fifth graderes of SDN 013 Balamjaya was still low.Thisis caused bythe applied learningtoday is stilldominatedbythe teacher. Teachersimplyuselesslectureandengage studentsin the learning processso thatstudentsare lessactiveanddo notwant toaskif they do notunderstand. Student's abilitytosolve problemsis lowthis can be seenfrom thestudents' understandingthatonlyfocused onthe examplesprovided by the teacher. Tofix this thing should be done by applying and appropriate learning model. One is theapplication ofcooperative learning modelNHT. The purpose of this study is to Improve Learning Resullt IPS Fourth Grade Elementary School District 013 Balamjaya Tambang by implementing cooperative learning model NHT. This type of research is Classroom Action Research (CAR), which was implemented in three cycles. Each cycle consists of planning, action, observation and reflection.The subject of this research is the fourth years SDN 013 Balamjaya with a number of students 32 people.The data obtained in this study are student learning resullt obtained through Deuteronomy Daily at the end of the cycle, all teachers have obtained from observation sheets teacher activity, student activity sheets obtained through observation of student activity.Analysis of student learning resullt on the basis of the average score of 63.43 and 34.38% mastery learning classical, Cycle I averaged 69.68 and 71.88% mastery learning classical, Cycle II averaged 77.03 with classical completeness 84.38,Cycle III averaged 84.21 and 93.75% classical completeness. From the results of this study concluded that with the implementation of cooperative learning model to improve learning resullt NHT IPS Elementary School fourth grade students 013Balamjaya Tambang District. Keywords : Numbered Heads Together (NHT), IPS Learning Result